Drug Utilization Study in Outpatient Department of Ophthalmology in Tertiary Care Hospital - Shrestha, U.; Shakya Shrestha, S.; Shrestha, A.; Poudel, U.; Manandhar Shrestha, J. T. (Kathmandu University Medical Journal, 2022)
Background The advancement in drug development and availability of newer drugs has improved overall health services including decrease in mortality and hospital stay. Along, it has brought negative impacts such as polypharmacy and associated adverse drug reactions and antimicrobial resistance. Drug utilization research is an essential approach to understand the drug use pattern, identify the early signs of such irrational drug use and to improve quality of drug use. Objective To study the drug utilization pattern in the Ophthalmology Outpatient department (OPD) of Dhulikhel Hospital, Kathmandu University Hospital (DH-KUH). Method A descriptive, cross sectional study was conducted from March 2019 to August 2019 in patients attending OPD of Ophthalmology in Dhulikhel Hospital, Kathmandu University Hospital. Prescriptions of 311 patients were analyzed using World Health Organization (WHO) International Network of Rational Use of Drug (INRUD) and additional other indices. The descriptive data was presented in mean and standard deviation. Result The average number of drugs per prescription was 2.10±1.35. Out of total 311 prescriptions, drugs prescribed in generic name were 152 (23.30%). Total antibiotics encountered were 247 (37.90%) and total drugs prescribed from National Essential Medicine List (NEML) were 371 (56.90%). Antibiotics 247 (37.90%) were the most commonly prescribed drugs followed by lubricants 146 (22.40%). Conclusion Practice of polypharmacy was very high. Most of the drugs were prescribed in brand names and antibiotics were the most frequently used drugs.